The Struggle for the Health Market Between Shamans and Doctors at the Beginning of the 20th Century - Misbahudin, Muhamad; Abdurahman, Dudung; Khuluq, Lathiful (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article explores and explains the struggle for the health market carried out by shamans and doctors in the Dutch East Indies. This health history research uses a sociological approach, using Michel Foucault's discourse theory of power as the unit of analysis. This article argues that shamans and doctors are not born and developed identities in a vacuum. They arise from conflicting social structures. Initially, this struggle between doctors and shamans never happened in the Dutch East Indies, especially in the Mangkunegaran area; they operated in different markets. The king who ruled in one of the Vostenlanden regions gave equal recognition to both as an entity in health. However, the spread of a new discourse about standardized hygiene, which continued to be promoted by the colonial government through European doctors, made people rethink their treatment choices. As discourses about cleanliness spread, scary stories also circulated about the failure of shamans to treat their patients. This situation has made the health market landscape in Vostenlanten begin to change. The discourse of cleanliness is constantly pushed into society, creating complicated interactions between shamans and doctors. On the other hand, religious organizations and Islamic studies, which initially did not discuss hygiene and health, began to become significant places to discuss, practice, and spread the combination of Javanese and Islamic culture in hygiene.